Risk Management in the Metal Casting Industry: Case in Ceper Klaten - Sadi, Sadi; Zuhrohtun, Zuhrohtun; Kusumawardhani, Indra (IPTEK Journal of Proceedings Series, 2020)
This study investigates the implementation of risk management in the metal casting industry. Previous research examines risk management in the production process, while this research identifies risk management in business processes. The research sample is 68 companies incorporated in Batur Jaya cooperatives, Ceper Klaten. This research uses survey method. Business risk management consists of four dimensions: business strategic risk, operational risk, reporting risk and regulatory risk. The results showed that the implementation of business strategic risk, operational risk and reporting risk were good enough. The implementation of regulatory risk management is the lowest compared to the other three risk management dimensions.